Emerging and legacy per- and polyfluoroalkyl substances in water, sediment, and air of the Bohai Sea and its surrounding rivers. (August 2020) - Zhao, Zhen; Cheng, Xianghui; Hua, Xia; Jiang, Bin; Tian, Chongguo; Tang, Jianhui; Li, Qilu; Sun, Hongwen; Lin, Tian; Liao, Yuhong; Zhang, Gan
Abstract: Per- and polyfluoroalkyl substances (PFASs) contamination in the Bohai Sea and its surrounding rivers has attracted considerable attention in recent years. However, few studies have been conducted regarding the distribution of PFASs in multiple environmental media and their distributions between the suspended particles and dissolved phases. In this study, surface water, surface sediment, and air samples were collected at the Bohai Sea to investigate the concentration and distribution of 39 targeted PFASs. Moreover, river water samples from 35 river estuaries were collected to estimate PFAS discharge fluxes to the Bohai Sea. The results showed that total ionic compound (Σ i -PFASs) concentrations ranged from 19.3 to 967 ng/L (mean 125 ± 152 ng/L) in the water and 0.70–4.13 ng/g dw (1.78 ± 0.76 ng/g) in surface sediment of the Bohai Sea, respectively. In the estuaries, Σ i -PFAS concentrations were ranged from 10.5 to 13500 ng/L (882 ± 2410 ng/L). In the air, ΣPFAS (Σi-PFASs + Σn-PFASs) concentrations ranged from 199 to 678 pg/m 3 (462 ± 166 pg/m 3 ). Perfluorooctanoic acid (PFOA) was the predominant compound in the seawater, sediment, and river water; in the air, 8:2 fluorotelomer alcohol was predominant. Xiaoqing River discharged the largest Σi-PFAS flux to the Bohai Sea, which was estimated as 12, 100 kg/y. Some alternatives, i.e., 6:2 fluorotelomer sulfonate acid (6:2 FTSA), hexafluoropropylene oxide dimer acid (HFPO-DA), and chlorinated 6:2 polyfluorinated ether sulfonic acid (Cl-6:2 PFESA), showed higher levels than or comparable concentrations to those of the C8 legacy PFASs in some sampling sites. The particle-derived distribution coefficient in seawater was higher than that in the river water. Using high resolution mass spectrometry, 29 nontarget emerging PFASs were found in 3 river water and 3 seawater samples. Further studies should be conducted to clarify the sources and ecotoxicological effects of these emerging PFASs in the Bohai Sea area. Graphical abstract: Image 1 Highlights: Thirty-nine PFASs were quantified in water, sediment and air from the Bohai Sea and its rivers. The K d between dissolved and particle phases in seawater were higher than those in river water. Discharge of total i -PFASs from 34 rivers was estimated to be 20.6 t/y. Twenty-nine novel PFASs were screening in sea and river water by HRMS. Abstract : This paper revealed the levels and composition of legacy and emerging PFASs in multiple environmental media of the Bohai Sea.